2015
DOI: 10.1149/2.0081508jss
|View full text |Cite
|
Sign up to set email alerts
|

Light Assisted Electrodeposition and Silicidation of Ni for Silicon Photovoltaic Cell Metallization

Abstract: Light assisted electrodeposition of Ni films was studied on crystalline Si photovoltaic cells. The nucleation, film uniformity and silicidation behaviour were studied at different locations across the busbar and were found to strongly depend on the plating solution, plating current and annealing conditions. The photovoltaic diode can be operated at forward bias or reverse bias during the light assisted electroplating depending on the plating current and light intensity. Suns-Voc of the solar cells was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…A light intensity of 17000 lux was used during plating except for the study on the light intensity effect. This light intensity was measured in an empty plating setup but 25 The total metal concentration, NiSO 4 and CoSO 4 , is therefore kept constant at 0.2 M. As shown in Table I, the ratio between the two metal species varies for different solutions in this study. A rapid thermal annealing (RTA) furnace with a thermal couple embedded in the carrier was used to anneal the NiCo plated solar cells to form silicide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A light intensity of 17000 lux was used during plating except for the study on the light intensity effect. This light intensity was measured in an empty plating setup but 25 The total metal concentration, NiSO 4 and CoSO 4 , is therefore kept constant at 0.2 M. As shown in Table I, the ratio between the two metal species varies for different solutions in this study. A rapid thermal annealing (RTA) furnace with a thermal couple embedded in the carrier was used to anneal the NiCo plated solar cells to form silicide.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported a study on the light assisted electroplating of Ni and the silicidation on silicon solar cells. 25 The uniformity of the Ni silicide formed from the electrodeposited Ni and the performance of the solar cell highly depended on the plating solution, light illumination, and the plating current density as well as the silicidation conditions. In this paper, light assisted electrodeposition of NiCo alloy was studied in conjunction with the light illumination intensity and the energy spectrum.…”
mentioning
confidence: 99%
“…Electrochemical processes at positive overpotentials (dissolution, etching, passivation, machining, and polishing) of Si, relevant to semiconductor technology, are widely reported in the literature. At the same time, processes at negative overpotentials have been rarely reported . These processes are of great importance to photoelectrochemical cells (PECs), Si-based electrochemical energy storage in lithium-ion batteries, and photoelectrochemical plating. Research activities on the cathodic reactions on Si have significantly increased in recent years. This is due to the industry’s initiative to employ cheaper materials for contacts in microdevices and photovoltaic applications. Since hydride formation and hydrogen evolution reaction (HER) occur at relatively low overpotentials in aqueous electrolytes, these reactions interfere with most of the cathodic processes on Si and often become detrimental to the final outcome. HER is also a process of enormous technological significance to produce pure hydrogen by electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…These processes are of great importance to photoelectrochemical cells (PECs), Si-based electrochemical energy storage in lithium-ion batteries, and photoelectrochemical plating. Research activities on the cathodic reactions on Si have significantly increased in recent years. This is due to the industry’s initiative to employ cheaper materials for contacts in microdevices and photovoltaic applications. Since hydride formation and hydrogen evolution reaction (HER) occur at relatively low overpotentials in aqueous electrolytes, these reactions interfere with most of the cathodic processes on Si and often become detrimental to the final outcome. HER is also a process of enormous technological significance to produce pure hydrogen by electrolysis. This process of producing hydrogen is considered to be an important option to store renewable energy. …”
Section: Introductionmentioning
confidence: 99%
“…14,18 In addition, the interface between the silicide and metal typically are not well controlled. A recent study showed that an additional Ni layer freshly plated after the removal of the excessive un-reacted Ni from the silicidation improves the interface and adhesion between the Ni silicide and Cu grid.…”
mentioning
confidence: 99%